2020
DOI: 10.1186/s13054-020-03419-y
|View full text |Cite
|
Sign up to set email alerts
|

Resuscitation fluid types in sepsis, surgical, and trauma patients: a systematic review and sequential network meta-analyses

Abstract: Background Crystalloids and different component colloids, used for volume resuscitation, are sometimes associated with various adverse effects. Clinical trial findings for such fluid types in different patients’ conditions are conflicting. Whether the mortality benefit of balanced crystalloid than saline can be inferred from sepsis to other patient group is uncertain, and adverse effect profile is not comprehensive. This study aims to compare the survival benefits and adverse effects of seven f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
33
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(38 citation statements)
references
References 30 publications
2
33
0
3
Order By: Relevance
“…Recently, a large, pragmatic randomized trial found that critically ill adult patients receiving balanced crystalloids had lower rates of the composite outcome of death and renal adverse events than those receiving saline ( 2 ). Our latest network meta-analysis also found a lower risk of mortality in sepsis patients treated with balanced crystalloids than in those treated with saline ( 3 ). In contrast, balanced crystalloids increased mortality in traumatic brain injury patients ( 3 ).…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…Recently, a large, pragmatic randomized trial found that critically ill adult patients receiving balanced crystalloids had lower rates of the composite outcome of death and renal adverse events than those receiving saline ( 2 ). Our latest network meta-analysis also found a lower risk of mortality in sepsis patients treated with balanced crystalloids than in those treated with saline ( 3 ). In contrast, balanced crystalloids increased mortality in traumatic brain injury patients ( 3 ).…”
Section: Introductionmentioning
confidence: 80%
“…Our latest network meta-analysis also found a lower risk of mortality in sepsis patients treated with balanced crystalloids than in those treated with saline ( 3 ). In contrast, balanced crystalloids increased mortality in traumatic brain injury patients ( 3 ). Therefore, both the fluid types and patient condition need to be considered when choosing an optimal fluid treatment.…”
Section: Introductionmentioning
confidence: 80%
“…hypoxic neurons, may have a beneficial effect for survival due to the ability of HES to inhibit formation of reactive oxygen species [ 8 ], whereas albumin can be deleterious for astrocyte or neuronal functions by modulating potassium ion and glutamate concentrations, which is driving epileptogenesis [ 13 15 ]. HA was associated with higher mortality rates in traumatic brain injury, in contrary HES showed better survival rates (sequential network meta-analyses of 26,351 patients [ 16 ]). In this context, the usage of HA for neurosurgery might also be discussed.…”
Section: Main Textmentioning
confidence: 99%
“…The infection range can affect the whole body, and it is often the common complication after severe trauma, critical illness, infection and major surgery. It usually causes functional damage to important tissues and organs (liver, kidney, lung), and further deterioration will lead to tissue hypoperfusion and continuous hypotension, which in turn develops into severe sepsis and septic shock ( 1 4 ). Sepsis has a very important connection with trauma.…”
Section: Introductionmentioning
confidence: 99%